2019
DOI: 10.1021/acs.langmuir.8b03176
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Membrane Distribution of Fluorescent Derivatives of Ceramide

Abstract: Ceramide is a bioactive lipid with significant roles in several biological processes including cell proliferation, apoptosis, and raft formation. Although fluorescent derivatives of ceramide are required to probe the behavior of ceramide in cells and cell membranes, commercial fluorescent ceramide derivatives do not reproduce the membrane behavior of native ceramide because of the introduction of bulky fluorophores in the acyl chain. Recently, we developed novel fluorescent analogs of sphingomyelin in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…While the pure SM GUVs formed a homogeneous gel phase (Figure 1a), SM/Cer GUVs underwent phase separation between ceramide-rich and ceramidepoor phases, which were visualized as dark and green domains, respectively (Figure 1b), using a fluorescent-lipid analogue (Bodipy-PC) as a marker of the ceramide-poor phase. 21 This result is in line with previous microscopic observations. 22,23 Interestingly, a similar phase separation was observed for Ceranalogues (Figure 1c−e), indicating that the substitution of the 1-OH group by NHAc, N 3 , or NH 2 does not significantly affect their domain formation in pure water (pH 7).…”
Section: ■ Results and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…While the pure SM GUVs formed a homogeneous gel phase (Figure 1a), SM/Cer GUVs underwent phase separation between ceramide-rich and ceramidepoor phases, which were visualized as dark and green domains, respectively (Figure 1b), using a fluorescent-lipid analogue (Bodipy-PC) as a marker of the ceramide-poor phase. 21 This result is in line with previous microscopic observations. 22,23 Interestingly, a similar phase separation was observed for Ceranalogues (Figure 1c−e), indicating that the substitution of the 1-OH group by NHAc, N 3 , or NH 2 does not significantly affect their domain formation in pure water (pH 7).…”
Section: ■ Results and Discussionsupporting
confidence: 93%
“…To compare the domain formability between Cer and its analogues (inclusively termed Cers), we prepared giant unilamellar vesicles (GUVs) composed of palmitoyl-sphingomyelin (SM) and Cers (95:5 and 90:10 mol/mol) binary mixtures and visualized the formation of ceramide-rich phase at 25 °C. While the pure SM GUVs formed a homogeneous gel phase (Figure a), SM/Cer GUVs underwent phase separation between ceramide-rich and ceramide-poor phases, which were visualized as dark and green domains, respectively (Figure b), using a fluorescent-lipid analogue (Bodipy-PC) as a marker of the ceramide-poor phase . This result is in line with previous microscopic observations. , Interestingly, a similar phase separation was observed for Cer-analogues (Figure c–e), indicating that the substitution of the 1-OH group by NHAc, N 3 , or NH 2 does not significantly affect their domain formation in pure water (pH 7).…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Because saturated sphingolipids increase acyl-chain order in the domains they form, among themselves and together with glycerophospholipids and cholesterol, methods that can detect changes in acyl-chain order are often used to detect the lateral segregation of ordered domains. For bilayer membranes, DSC (49), 2 H NMR (50,51), fluorescence spectroscopy (30,31,35,52,53), and microscopy (54,55) have been successfully used to detect the lateral segregation of ordered domains. The fluorescent probe tPa is excellent for detecting the lateral segregation of sphingolipid-rich domains, which have an increased acyl-chain order when compared to the surrounding fluid glycerophospholipid bilayer.…”
Section: Discussionmentioning
confidence: 99%
“…First, he developed a concise method to quantitatively measure the interaction between lipids and MPs (Inada et al 2019b) and revealed that MP-specific lipids have strong effects on the structure and function of MPs (Inada et al 2019a). Second, he is investigating the molecular basis of lipid raft formation by developing new fluorescent derivatives of raft-related lipids (Kinoshita et al 2017;Matsufuji et al 2019). He also explores the actions of drugs and toxins on membranes and/or MPs.…”
mentioning
confidence: 99%